Study on the Performance of Fan-coil Unit in a Moderate Water Temperature Air Conditioning System - Bai Mengmeng; Wang Fenghao; Wang Zhihua; Ma Ruixue; Li Ke (Zhileng xuebao)
In this paper, the variation in the indoor temperature and humidity when FP85 series fan-coil units are used to treat indoor return air to its equilibrium point is analyzed based on the experimental comparison between an air conditioning system with a moderate water temperature and a conventional air conditioning system. Then, the influence of a chilled water supply temperature and tube numbers on the heat transfer performance of a fan-coil unit is simulated and analyzed by a coil simulation method. The experimental results show that when the temperature of the chilled water supply increased from 7 °C to 9 °C, the latent heat capacity of the 3-row FP85 fan-coil unit was reduced. As a result, the indoor humidity cannot be guaranteed in the comfortable range. As the chilled water supply was increased by 1 °C, the relative humidity of the indoor equilibrium point increased by 11.03%–12.05% accordingly. For the 6-row FP85 fan-coil unit, the temperature and humidity of the indoor equilibrium state can meet the design requirements of comfortable air conditioning,system with a chilled water supply temperature in the range of 9–12 ℃. Moreover, the simulation results state that the 4-row, 5-row, and 6-row FP85 fan-coil units can ensure an equilibrium indoor temperature and humidity in the comfortable range for an indoor return air with dry bulb temperature 27.01 °C and wet bulb temperature 19.51 °C, respectively. The heat exchange and dehumidification coefficients of the 4-row fan-coil unit decreased by 6.13% and 0.045, respectively, when the supply chilled water temperature increased by 1 °C. The heat transfer coefficient and dehumidification ability of the 4-row fan-coil unit are superior to that of the 5-row and 6-row fan-coil units. Therefore, the 4-row FP85 fan-coil unit is more appropriate for an air conditioning system with moderate water temperature. This study indicates that the air conditioning system with moderate water temperature has great application potential, and provides a theoretical basis for the design of air conditioning system with moderate water temperature.